PEMANFAATAN MEDIA SOSIAL DALAM MODERASI BERAGAMA DI MASA PANDEMI COVID-19: PENTINGNYA MENGHARGAI DAN BERTOLERANSI ATAS PERBEDAAN DENGAN AGAMA LAIN - Najib, M Ainun (Moderatio: Jurnal Moderasi Beragama, 2021)
Indonesia is a country with a multicultural society that becomes an extraordinary social force if we are open-minded to each other and work together in the differences that exist. The development of technology and information in the 4.0 era can be used to convey data more effectively and quickly through social media. Moderation must be done by paying attention to each other to practice the ability to manage differences. Tolerance is a form of accommodation in social interaction. Religious tolerance is tolerance that includes issues of belief in humans related to the faith or divinity that they believe in